2017
DOI: 10.1111/phpp.12359
|View full text |Cite
|
Sign up to set email alerts
|

Repeated ultraviolet irradiation induces the expression of Toll‐like receptor 4, IL‐6, and IL‐10 in neonatal human melanocytes

Abstract: These results suggest that human melanocytes may actively participate in UV-induced immune modulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
11
0
2
Order By: Relevance
“…UVB induces a number of cytokines in different cell types, of which IL-6, IL-8, and CXCL-1 are known to respond in primary melanocytes (Song et al, 2018), and CXCL-10 was first found here. Our findings show that the four mediators induced by UVB were further up-regulated by depolymerization of hyaluronan and that IL8 and CXCL1 responded to melanocyte hyaluronan coat disturbance even in the absence of UVB.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…UVB induces a number of cytokines in different cell types, of which IL-6, IL-8, and CXCL-1 are known to respond in primary melanocytes (Song et al, 2018), and CXCL-10 was first found here. Our findings show that the four mediators induced by UVB were further up-regulated by depolymerization of hyaluronan and that IL8 and CXCL1 responded to melanocyte hyaluronan coat disturbance even in the absence of UVB.…”
Section: Discussionmentioning
confidence: 62%
“…UVR is the main risk factor for skin melanoma (Valejo Coelho et al, 2016). Although UVA (320À400 nm) may be immunosuppressive (Dupont et al, 2013), UVB (280À320 nm) promotes inflammation, apoptosis, the activation of immune cells, and the secretion of various cytokines and chemokines, such as IL-6, IL-10, and IFN-inducible protein 10 (i.e., IP-10/CXCL-10) (Aoki and Moro, 2005;Song et al, 2018). During melanoma progression, the increased secretion of IL-6 and IL-8 supposedly drives cell proliferation and invasion (Lazar-Molnar et al, 2000;Schadendorf et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…TLR4 activation by LPS induces the expression of tyrosinase and its transcription factor MITF in melanocytes via the activation of p38 MAPK (mitogen-activated protein kinase) [51] (Figure 4, Table 1). In human neonatal melanocytes, repeated UV irradiation increases TLR4 expression and pigmentation [93]. LPS stimulation with repeated UV irradiation induces IL-6 secretion from human neonatal melanocytes, suggesting that melanocytes participate in UV-induced immune modulation [93].…”
Section: Tlr4 and Melanocyte Functionsmentioning
confidence: 99%
“…Stimulation of melanocytes with lipopolysaccharide (LPS), a major component of the cell wall of Gram‐negative bacteria, upregulated the expression of TLR4 and MyD88 mRNA, activated the central transcription factor NF‐κB and enhanced the expression of some proinflammatory cytokines and chemokines . It was also found that TLR4 expression in melanocytes was upregulated by repeated low‐dose UVA or UVB irradiation …”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest a role of TLRs in the modulation of melanogenesis and in microbial‐ or inflammation‐related changes in skin pigmentation. It was demonstrated that the activation of TLR4 increased melanin synthesis in human melanocytes and induced pigmentation of cultured skin . Similarly, the stimulation of TLR2, TLR3 and TLR9 with their agonists enhanced melanogenesis in melanocytes, while activation of TLR5 and TLR7 reduced melanin content of melanocytes and inhibited body pigmentation of zebrafish embryos …”
Section: Introductionmentioning
confidence: 99%